Transforming the Chaos: The ‘Writing’ Experiments of the Postdigital Ludic Writer - Katy Wareham Morris (Anglica. An International Journal of English Studies)
The multimodal writer does not simply write a poem or piece of fiction, but also architects a dynamic, ludic space in order to ‘publish’ the piece. This article examines the literature associated with “literary-ludic hybridity” (Ensslin 32–33) whilst also offering critical reflections on my own playful experiments in digital writing, namely in the creation of Viole(n)t Existence. This process of autoethnographic evaluation revealed that some of the precise writing challenges faced by multimodal, literary-ludic writers were not examined as closely as those of ‘traditional’ print writers. Whilst Barnard (2017) acknowledges that both hardware and software date quickly and multimodal writers must be invested in new innovations, the implications are not fully elucidated. The realities are that this hardware and software can change even before the creative piece is finished. From my own experience, the creative process evolved to be far more complex than that captured by the terms ‘drafting’ or ‘editing.’ It involved producing and assessing a collection of iterations which move between digital and physical spaces, and blur digital, personal and cultural bodies, whilst trying desperately, ultimately phantasmorgorically, to move towards an ever elusive ‘final’ piece. This form of writing practice demonstrates Alexenberg’s (10) understanding of the postdigital. Postdigital ludic writers must engage in many playful, creative experiments, thus simultaneously creating postdigital, posthuman archives, which are all in constant metamorphosis.